Web application for pharmacy information system - Cheng, Min (2014)
The main purpose of this project is to build a Web Based Pharmacy Information System, which helps user to manage the pharmacy data in different hospitals in a region. It aims at helping user to save cost and time on pharmacy management. The whole system is made up of five major components: Category Management, Medicine Management, In Store Management, Out Store Management and Storage tracking with some accessory functions such as Customize Printing Page and so on.